Anatomy of the brain of capybara (Hydrochoerus hydrochaeris) using magnetic resonance imaging - da Silva Alves, Lidiane [UNESP]; Vulcano, Luiz Carlos [UNESP]; Girotto, Carolina Hagy [UNESP]; de Castro Sasahara, Taís Harumi [UNESP]; Schimming, Bruno Cesar [UNESP] (Wiley, 2024)
Capybara is considered the largest living rodent and is widespread distributed in the South America and in the Brazilian territory. The purpose of this study was to provide the anatomical description of the brain in the capybara (Hydrochoerus hydrochaeris) using magnetic resonance imaging (MRI). Brains of ten normal capybaras were imaged and sectioned in the anatomical studies. MRI was acquired on 0.25 Tesla equipment, promoting good-quality images capable to identify and classify the main anatomical structures of clinical interest. MRI reference images were validated by comparing them with gross anatomical sections. The capybara sulci and gyri were named for its similar location and orientation to those described in the previous descriptions in the capybara and in the domestic dog. Capybaras presented prominent cerebral sulcus and gyrus in relation to other caviomorph rodents, but in reduced number when compared to domestic animals and other wild mammals such as elephants and giraffes. The findings of this study indicate that the shape of the capybara brain is remarkably similar to that of the caviomorph rodents with a higher neocortilization. The capybara rhinencephalon was well-developed implying a good sense of smell. Due to this development of the rhinencephalon, we can suggest that capybara brain is a macrosmatic brain. The MRI and gross anatomical sections of capybara brain may help veterinary researchers and clinicians increase the accuracy of brain MRI scans interpretation in these animals.
Keywords: anatomy; caviomorphs; central nervous system; diagnostic imaging; head; rodents